Applying a logistic growth equation to model flocculation of sediment in the presence of living and dead organic matter - Safar, Zeinab; Deng, Zhirui; Chassagne, Claire (Frontiers in Marine Science, 2023)
In the present study we are aiming to parameterize a flocculation model, based on an logistic growth equation, by conducting laboratory experiments. The flocculation experiments are performed using two types of natural sediments and different flocculating agents: salt (monovalent and divalent), extracellular polymeric substances (EPS), living and dead microalgae Skeletonema Costatum. It was found that the median size of flocs (D50) did not exceed the Kolmogorov microscale when salt-induced flocculation was performed (in the absence of organic matter), in line with previous studies. Flocs with organic matter reach sizes that are larger than the Kolmogorov microscale and both their growth and steady-state size are salinity-dependent. Divalent salts in particular are shown to promote flocculation of sediment to organic matter. The logistic growth model can be used to study either the evolution of a class volume concentration as function of time, or the change in size of a given class as function of time. The fine particles volume concentration decreases in time while the coarse particle volume concentration increases, during the flocculation process. The mass balance between two of the classes defined in [Chassagne C, Safar Z. Modelling flocculation: Towards an integration in large-scale sediment transport models. Marine Geology. 2020 Dec 1;430:106361] is estimated.